Deskripsi Kemampuan Berpikir Kritis Siswa dengan Menggunakan Model Pembelajaran Problem Based Learning - Dedi Susanti Mendrofa; Agnes Renostini Harefa; Desman Telaumbanua; Novelina Andriani Zega (Journal on Education, 2024)
The background to the implementation of this research was the low critical thinking skills of students at SMP Negeri 1 Hiliserangkai. The objectives of this research are: (1) To determine students' critical thinking abilities in science learning using the Problem Based Learning learning model at SMP Negeri 1 Hiliserangkai. (2) Describe the learning process using the Problem Based Learning learning model in science learning at SMP Negeri 1 Hiliserangkai. The instruments used in this research are: (1) Test of students' critical thinking abilities, (2) Questionnaire sheet for students' critical thinking abilities, (3) Observation sheet to observe the learning process. Research results: (1) The critical thinking ability of students in science learning using the Problem Based Learning learning model is an average value (mean) of 73.76 in the good category, the standard deviation is 7.805 and for each indicator of critical thinking ability is at the stage of providing a simple explanation was obtained by 85.93%, the stage of building basic skills was obtained by 84.41%, the stage of making inferences or conclusions was 79.59%, the stage of making further explanations was obtained by 82.76%, and the stage of organizing strategies and technique obtained a percentage of 81.38%. (2) The learning process using the Problem Based Learning learning model in science learning at SMP Negeri 1 Hiliserangkai obtained results of 86.96% classified as Good.